2013
DOI: 10.1002/pd.4153
|View full text |Cite
|
Sign up to set email alerts
|

Age independent first trimester screening for Down syndrome: improvement in test performance

Abstract: The AR method results in a significant decreased likelihood of receiving a false prediction with a comparable likelihood of receiving a true prediction. Thus, fewer invasive diagnostic tests will be performed. It will take away the misunderstanding about differences in screening performance for women of different ages. This might lead to a higher uptake of first trimester screening resulting in a more efficient screening policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The conclusions of the study are that the age related risk assessment algorithm could be optimized, but also that the screening test works very well in detecting trisomy 21 among ''older women''. There are recent studies that underline the age-independent accuracy of the combined test in screening for trisomy 21 [13] and that have recently reviewed and questioned the use of invasive procedures based on maternal age only [14][15][16][17]. This evidence was the background for the conception of our study, and combined with our findings, seems to warrant the extensive application of the combined test in the general population of pregnant women irrespective of maternal age.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The conclusions of the study are that the age related risk assessment algorithm could be optimized, but also that the screening test works very well in detecting trisomy 21 among ''older women''. There are recent studies that underline the age-independent accuracy of the combined test in screening for trisomy 21 [13] and that have recently reviewed and questioned the use of invasive procedures based on maternal age only [14][15][16][17]. This evidence was the background for the conception of our study, and combined with our findings, seems to warrant the extensive application of the combined test in the general population of pregnant women irrespective of maternal age.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion our data have clearly demonstrated that the first trimester screening of trisomy 21 by mean of the combined test is a highly effective method and allows a sensible decrease of costs and healthy miscarriage in comparison with the policy of direct invasive testing among pregnant women aged 35 or more. The risk of missing a case of trisomy 21 with this screening protocol is very low in ''older women'' and according to the recent literature this seems to be actually lower than in younger patients [13]. On this basis, the option of implementing a national universal screening policy based on the combined test and abandoning the direct access to prenatal diagnosis based on maternal age should be strongly considered across the western world.…”
Section: Discussionmentioning
confidence: 97%
“…This increase reflected a gradual change in clinic policy to accept patients with more advanced gestations, more requests for late termination of pregnancy because of fewer options being available elsewhere, and advances in fetal diagnosis. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] More than 95% of patients in this series of 1005 patients had uncomplicated pregnancy terminations with complete evacuation of the uterus The 26 patients presenting with a spontaneous fetal demise late in pregnancy were managed by a D & E procedure following serial multiple laminaria dilation of the cervix. For 12 patients with a single live abnormal fetus, fetal demise was induced at the patient′s request followed by management of the delivery by the patient′s own obstetrician.…”
Section: Resultsmentioning
confidence: 97%
“…The current standard of prenatal care involves a first trimester combined screening or integrated prenatal screening in conjunction with second trimester fetal ultrasound scan to identify pregnancies at risk for chromosomal abnormalities and fetal structural abnormalities. Recently noninvasive prenatal screening has emerged using cell free fetal (cff) DNA in maternal circulation .…”
Section: Introductionmentioning
confidence: 99%